RADT-09. PREOPERATIVE STEREOTACTIC RADIOSURGERY FOR LARGE CEREBRAL METASTASES – A PROSPECTIVE CLINICAL TRIAL SHOWING EFFICACY AND DECREASED TIME TO RESUMPTION OF IMMUNOTHERAPY. (14th November 2022) - Mallela, Arka; Iheagwara, Uzoma; Fogg, David; Anthony, Austin Walker; Zhang, Xiaoran; Gersey, Zachary; Abou-Al-Shaar, Hussam; Xu, Emily; Zinn, Pascal; Burton, Steve; Quinn, Annette; Clump, David; et al.
Abstract: INTRODUCTION: Preoperative stereotactic radiosurgery (SRS) is an emerging therapeutic strategy for treatment of brain metastasis requiring surgical resection. Prior reports have been highly-controlled, excluding very large brain metastases. Here, we report a prospectively-collected preoperative series reflective of a real-world neurosurgical patient cohort, with a particular focus on resumption of immunotherapy. METHODS: Our series included Nf27 prospective preoperative compared to concurrently collected Nf37 postoperative patients. Demographic, SRS volumes/dose, pre/postoperative immunotherapy, and clinical outcomes were collected. Subsequent univariate comparisons between groups were performed. RESULTS: Pre/postoperative tumor volumes (19.1 [range: 2.4-65.1] vs. 12.5 [3.6-80.3]cc, p=0.20); local tumor control at 1 year (77.6% vs. 71.4%, p=0.616); overall survival (1.0 [0.8-2.2] vs. 1.3 [0.7-NR] years, p=0.8) were comparable between groups. Rates of LMD (3.7% vs. 8.0%, p=0.39) and subsequent WBRT (8.0% vs. 16.2%, p=0.46) were not statistically different. OR time (168 vs. 173 min, p=0.64), estimated blood loss (133 vs. 180 mL, p=0.31), and wound infections (1 vs. 1, p=1.00) were not significantly different.An ostensible advantage to preoperative SRS is that steroids may be weaned more quickly to allow resumption of immunotherapy. Median steroid taper length was significantly shorter (8 vs. 21.5 days, p=0.007), and median daily Dexamethasone dose at 1 week post-op was significantly lower in the preoperative group (1 vs. 7mg d, p=0.007). All preoperative patients eligible for resumption of immunotherapy (Nf5) resumed treatment within 6 weeks. Conversely, only 2/6 in postoperative patients resumed treatment within 6 weeks, (p=0.07), while 4 failed to resume immunotherapy altogether. In patients initiating immunotherapy after OR/SRS, time to initiation was non-significantly lower in the preoperative group (52[38-84] vs.163[108-208] days, p=0.06). CONCLUSIONS: Preoperative SRS is safe and provides comparable local tumor control rate even in large tumors ( >20cc). In patients requiring resumption of immunotherapy, preoperative SRS may provide a faster pathway towards resumption of systemic therapy.